A critical assessment of the swarnajayanti gram swarojagar yojana in india - Sarkar, Susmita; Kumar, K.R Mahesh (International research journal of management, IT and social sciences, 2016)
The present study is a critical assessment of Swarnajayanti Gram Swarojagar Yojana (SGSY), a national level anti-poverty program of the government of India with regard to poverty eradication and women's empowerment. Though the SGSY scheme focuses only on poverty reduction and does not have explicit gender equality objectives, however, number of women members and women Self-help groups are encouraged to be linked with this program than men. The Ministry of Rural Development, Government of India, constituted a committee on credit-related issues under SGSY to analyze the constraints in the adequate flow of credit to Self-help groups of SGSY and to suggest measures and strategies for promoting effective credit linkages to the SHGs and made two strategies of universalization coverage of SHGs assisted by bank credit and providing skills at least to one youth of a Below Poverty Line (BPL) family necessitates restructuring of SGSY.